2005
DOI: 10.1186/1471-2105-6-215
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic covariation between gene expression and proteome characteristics

Abstract: Background: Cells react to changing intra-and extracellular signals by dynamically modulating complex biochemical networks. Cellular responses to extracellular signals lead to changes in gene and protein expression. Since the majority of genes encode proteins, we investigated possible correlations between protein parameters and gene expression patterns to identify proteome-wide characteristics indicative of trends common to expressed proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Integrative analysis of different types of data is widely applied to construct regulatory gene networks [ 2 , 3 ], overall improving the predictive power of such networks [ 4 ]. It has been shown that indirect indications of functional relevance between genes such as gene co-expression and genome co-localization are largely complementary and correlate well with ontology-based protein groupings [ 5 , 6 ]. However, not all interactions correlate well: genetic and protein interactions barely overlap [ 7 ], that causes some obvious challenges in retrieving useful information from a reconstructed species-specific network.…”
Section: Introductionmentioning
confidence: 99%
“…Integrative analysis of different types of data is widely applied to construct regulatory gene networks [ 2 , 3 ], overall improving the predictive power of such networks [ 4 ]. It has been shown that indirect indications of functional relevance between genes such as gene co-expression and genome co-localization are largely complementary and correlate well with ontology-based protein groupings [ 5 , 6 ]. However, not all interactions correlate well: genetic and protein interactions barely overlap [ 7 ], that causes some obvious challenges in retrieving useful information from a reconstructed species-specific network.…”
Section: Introductionmentioning
confidence: 99%